Hikayat Pattani dan Eksistensi Masjid di Negeri Pagoda: Umat Islam Thailand dalam Pusaran Harmoni dan Konflik - Tri Ramadhan (Journal of Islamic Civilization, 2021)
Thailand is one of the most famous kingdoms in Southeast Asia that still exists today. The Kingdom of Thailand comes from the original name “Muang Thai” (formerly called Siam). Islam grew in Thailand is the fruit of a long process. Since the 9th century, Islam has entered Thai society with limited conditions. Islamic teachings have grown and existed in Thailand through various historical events from the classical period (9th century) to modern times (early 21st century). This study aims to explore the history of the development of Islam and the conflicts that occurred in Thailand. The research method used in this article is a critical historical method with a literature study approach. The description of the conflict and its accommodation process that occurred in Thailand is expected to be used as an additional academic reference and an example for relevant stakeholders to stimulate inter-religious harmony in Indonesia, given the issues of tolerance and radicalism that had surfaced. Thailand merupakan salah satu kerajaan tersohor di Asia Tenggara yang masih eksis hingga saat ini. Kerajaan Thailand berasal dari nama asli “Muang Thai” (sebelumnya disebut Siam). Agama Islam tumbuh di Thailand merupakan buah dari proses yang cukup panjang. Sejak abad ke 9, Islam sudah masuk ke masyarakat Thailand dengan kondisi terbatas. Ajaran Islam telah tumbuh dan eksis di Thailand melalui berbagai peristiwa sejarah dari masa klasik (abad 9) hingga masa modern (awal abad 21). Penelitian ini bertujuan mengeksplorasi sejarah perkembangan Islam, asimilasi, dan konflik yang terjadi di Thailand. Metode penelitian yang digunakan dalam artikel ini adalah metode sejarah kritis dengan pendekatan studi kepustakaan. Deskripsi konflik dan proses akomodasinya yang terjadi di Thailand diharapkan dapat dijadikan sebagai referensi akademis tambahan dan salah satu contoh bagi stakeholder terkait untuk menstimulasikan kerukunan antar umat beragama di Indonesia mengingat isu toleransi dan radikalisme sempat mengemuka.